The Postpharyngeal Gland: Specialized Organ for Lipid Nutrition in Leaf-Cutting Ants - Decio, Pamela [UNESP]; Vieira, Alexsandro Santana [UNESP]; Dias, Nathalia Baptista [UNESP]; Palma, Mario Sergio [UNESP]; Bueno, Odair Correa [UNESP] (Public Library Science, 2016)
There are several hypotheses about the possible functions of the postpharyngeal gland (PPG) in ants. The proposed functions include roles as cephalic or gastric caeca and diverticulum of the digestive tract, mixing of hydrocarbons, nestmate recognition, feeding larvae, and the accumulation of lipids inside this gland, whose origin is contradictory. The current study aimed to investigate the functions of these glands by examining the protein expression profile of the PPGs of Atta sexdens rubropilosa (Hymenoptera, Formicidae). Mated females received lipid supplementation and their glands were extracted and analyzed using a proteomic approach. The protocol used combined two-dimensional electrophoresis and shotgun strategies, followed by mass spectrometry. We also detected lipid beta-oxidation by immunofluorescent marking of acyl-CoA dehydrogenase. Supplying ants with lipids elicited responses in the glandular cells of the PPG; these included increased expression of proteins related to defense mechanisms and signal transduction and reorganization of the cytoskeleton due to cell expansion. In addition, some proteins in PPG were overexpressed, especially those involved in lipid and energy metabolism. Part of the lipids may be reduced, used for the synthesis of fatty alcohol, transported to the hemolymph, or may be used as substrate for the synthesis of acetyl-CoA, which is oxidized to form molecules that drive oxidative phosphorylation and produce energy for cellular metabolic processes. These findings suggest that this organ is specialized for lipid nutrition of adult leaf-cutting ants and characterized like a of diverticulum foregut, with the ability to absorb, store, metabolize, and mobilize lipids to the hemolymph. However, we do not rule out that the PPG may have other functions in other species of ants.